V Anniversary International Medical Forum - journal "Morphologia", Editorial office (Морфологія / Morphologia / Morfologìâ, 2014)
V-JUBILEE INTERNATIONAL MEDICAL FORUM - a large-scale complex event of the innovative direction of the health care sector of Ukraine, which brings together the scientific-practical program, schools, exhibitions and specialty-events, will take place on October 14-16, 2014 in Kyiv (KyivExpoPlaza Center). lined exhibitions and creates an international platform for the exchange of experience and advanced training of health professionals.